The Construction of Crime: The Presumption of Blue-Collar Guilt and White-Collar Innocence. Issue 2 (6th April 2016) - Marriott, Lisa
Abstract : This study examines a recent legislative change in New Zealand social policy that provides for the partners of people engaging in welfare fraud to be prosecuted for the crime and to be jointly liable for the debt generated from the crime. This situation applies where the partner knew, or ought to have known, of the fraud. This approach may be contrasted with the treatment of the partners of those who engage in tax evasion, or other forms of financial crime, who are not liable for prosecution or any debt resulting from the offence. Discrimination of those on welfare is well-established. The article highlights the extent to which welfare beneficiaries are now targeted for greater punitive measures in New Zealand and the increasing criminalisation of welfare in the country. The practices outlined appear to contravene the New Zealand Human Rights Act. Moreover, these practices are not aligned with the basic provisions of criminal law: that a guilty mind and a positive act are present for a crime to be committed. The study draws attention to issues of equity, knowledge of crime, and the construction of crime and criminals in the New Zealand justice system.